Influence of mortar joints on the behaviour of FRP materials bonded to different masonry substrates. (15th December 2017) - Ceroni, F.; Leone, M.; Rizzo, V.; Bellini, A.; Mazzotti, C.
Highlights: Experimental bond tests of FRP materials bonded on different masonry substrates. Assessment of the influence of mortar joints. Design by testing procedure for the debonding load of FRP materials bonded to masonry substrates. Abstract: The use of epoxy bonded fibre reinforced polymer (FRP) materials as strengthening technique for existing masonry structures is becoming in the last years more and more widespread, but some topics, as the effect of the mortar joints on the bond performance at the reinforcement/masonry substrate interface, still represents an open question. This paper is focused on studying in detail the effect of the mortar joints on the bond performance of FRP materials made of different type of fibres (carbon, glass, basalt, steel) externally bonded by means of epoxy resin to three different masonry substrates, very common in Italy: tuff stones, Lecce stones, and clay bricks. Firstly, the experimental results of bond tests carried out by three laboratories on three different masonry substrates were discussed in detail in order to highlight the effect of the mortar joints as the masonry typology changes. Successively, statistical analysis were performed on a more extended database of bond tests coming from literature and carried out on similar masonry substrates. The analysis were aimed to define design formulations for calculating the debonding load of FRP materials bonded to different masonry substrates with and without mortar joints.